Determinación de biomasa mediante una ecuación alométrica para altura total en bosque de colina baja, distritos de Mazán Y Napo, Loreto, Perú. 2024 - Valdivia Quintero, Hillary Scay (2024)
An allometric formula was used to calculate biomass, aimed at estimating total tree height in a low hill forest in the consolidated contracts Tacsha 01 - 16-IQU/C-J-170- 04, 16-IQU/C-J-217-04, 16-IQU/C-J-243-04, 16-IQU/D-C-001-12, 16-IQU/C-J-171- 04, 16-LOR-MAY/CON-MAD-2018-006 and 16-LOR-MAY/CON-MAD-2018-009, located in the districts of Mazán and Napo, in Loreto, Peru. Floristic diversity is evidenced by the presence of 7460 trees belonging to 60 species and 20 botanical families. The cubic model (AT = 8,751 + (0,368 x DAP) + (-0,004 x DAP2) + (0,00001371 x DAP3)) proved to be the most adequate to calculate the total height of the trees according to DBH, with coefficients of determination R2 of 0,992, adjusted R2 of 0,989 and a standard error of estimation SEE of 0,328. The total biomass reached 22509,88 kg/ha. Eschweilera albiflora and Iryanthera elliptica stand out for their higher biomass, registering 3967,11 kg/ha and 2728,90 kg/ha, respectively. The research rules out the hypothesis that the linear allometric model is not suitable for estimating the total tree height in the low hill forest.